What Is There in Seeds? Vertically Transmitted Endophytic Resources for Sustainable Improvement in Plant Growth - Shahzad, Raheem; Khan, Abdul L.; Bilal, Saqib; Asaf, Sajjad; Lee, In-Jung (Frontiers in Plant Science, 2018)
Phytobeneficial microbes, particularly endophytes, such as fungi and bacteria, are concomitant partners of plants throughout its developmental stages, including seed germination, root and stem growth, and fruiting. Endophytic microbes have been identified in plants that grow in a wide array of habitats; however, seed-borne endophytic microbes have not been fully explored yet. Seed-borne endophytes are of great interest because of their vertical transmission; their potential to produce various phytohormones, enzymes, antimicrobial compounds, and other secondary metabolites; and improve plant biomass and yield under biotic and abiotic stresses. This review addresses the current knowledge on endophytes, their ability to produce metabolites, and their influence on plant growth and stress mitigation.